Development of social skills for people with ASD through intervention with digital technologies and virtual reality (VR) tools (Research, Society and Development, 2023)
This analysis explores the use of virtual reality (VR) tools as an intervention to improve social skills for individuals with Autism Spectrum Disorder (ASD). The analysis aims to understand the effectiveness of VR tools in providing a safe and controlled environment for individuals with ASD to practice social skills, in comparison to traditional interventions such as role-playing and group therapy.The findings of the study suggest that VR intervention is more effective in improving social skills for individuals with ASD compared to traditional interventions. The VR intervention found to be engaging, enjoyable, and immersive for participants, and they reported feeling more confident in social situations.The analysis also discusses the practical implications of VR intervention for individuals with ASD, such as reducing the stigma associated with traditional therapy, and the potential for individualized and customizable interventions. Additionally, raises important ethical considerations such as the need for informed consent, privacy, and confidentiality when using VR tools in interventions for individuals with ASD. The objectives of this research publication are to comprehensively analyze the literature on interventions aimed at improving social skills in individuals with ASD and identify gaps in current research. Additionally, this research aims to explore the potential of digital technologies and virtual reality (VR) tools as effective and innovative methods for enhancing social skills in individuals with ASD. The publication also aims to critically evaluate the effectiveness of digital technologies and VR tools in improving social skills in individuals with ASD, based on existing empirical evidence. Further, the publication aims to provide practical recommendations for the design and implementation of digital technologies and VR interventions aimed at improving social skills in individuals with ASD. Additionally, this research publication aims to highlight the potential benefits of using digital technologies and VR tools in interventions aimed at improving social skills in individuals with ASD, including increased motivation, engagement, and generalization of skills. Furthermore, ethical considerations associated with using digital technologies and VR tools in interventions aimed at improving social skills in individuals with ASD will be discussed, including issues related to privacy, safety, and informed consent. Lastly, this research aims to identify areas for future research and development in the field of digital technologies and VR interventions for individuals with ASD, with a focus on improving social skills and overall quality of life.